2013
DOI: 10.1016/j.ultrasmedbio.2013.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Adenovirus Delivery after Ultrasound-Stimulated Therapy in a Cancer Model

Abstract: Improving the efficiency of adenovirus (Ad) delivery to target tissues has the potential to advance the translation of cancer gene therapy. Ultrasound (US)-stimulated therapy uses microbubbles (MBs) exposed to low-intensity US energy to improve localized delivery. We hypothesize that US-stimulated gene therapy can improve Ad infection in a primary prostate tumor through enhanced tumor uptake and retention of the Ad vector. In vitro studies were performed to analyze the degree of Ad infectivity after applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…For diagnostic US treatment, , the custom setup included a single element (1.90 cm in diameter) immersion transducer (Olympus, Waltham, MA) in series with a signal generator (AFG3022B, Tektronix, Beaverton, OR) and a power amplifier (A075, Electronics and Innovation, Rochester, NY). The following acoustic parameters were used: 2.25 MHz US frequency, 2.0 MPa pressure amplitude, 1000 cycle pulse length, 1.0 s pulse repetition period, and 3, 30, 180, 300, and 900 s duration of exposure.…”
Section: Methodsmentioning
confidence: 99%
“…For diagnostic US treatment, , the custom setup included a single element (1.90 cm in diameter) immersion transducer (Olympus, Waltham, MA) in series with a signal generator (AFG3022B, Tektronix, Beaverton, OR) and a power amplifier (A075, Electronics and Innovation, Rochester, NY). The following acoustic parameters were used: 2.25 MHz US frequency, 2.0 MPa pressure amplitude, 1000 cycle pulse length, 1.0 s pulse repetition period, and 3, 30, 180, 300, and 900 s duration of exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Although viral vectors were highlighted by their satisfactory transfection e ciency, lack of tissue targeted ability limit the administration route of viral vectors to local injection, which might cause tissue damage. Previous studies have proved that a tissue targeted effective gene transfection could be achieved through binding viral vectors to the surface of MBs with the aid of ultrasound irradiation [36,37]. In our latest research, we also demonstrated that ultrasound beam could destroy the virus loading MBs, release the viral vectors at ventricular level, and realize the tissue targeted gene delivery [22].…”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, MB sonication has been found to induce caveolae- and clathrin-dependent endocytosis in targeted cells29,30 thereby promoting uptake of i.a. viral particles31,32. Using our settings, we found transduction by lentiviral SO-Mag MMB to be mediated by caveolin-dependent endocytosis, potentially induced by sonication.…”
Section: Discussionmentioning
confidence: 75%